Omalizumab in allergic bronchopulmonary aspergillosis in patients with cystic fibrosis [Erratum] - Ashkenazi M (Journal of Asthma and Allergy, 2018)
Ashkenazi M, Sity S, Sarouk I, et al. J Asthma Allergy. 2018;11:101–107. On page 101, in the Conclusion section, the text “omlaizumb” should have been “omalizumab”. Read the original article.